Search for anomalous Wtb couplings and flavour-changing neutral currents in t-channel single top quark production in pp collisions at √s=7 and 8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2017)
Single top quark events produced in the t channel are used to set limits on anomalous Wtb couplings and to search for top quark flavour-changing neutral current (FCNC) interactions. The data taken with the CMS detector at the LHC in proton-proton collisions at √ s = 7 and 8 TeV correspond to integrated luminosities of 5.0 and 19.7 fb−1 , respectively. The analysis is performed using events with one muon and two or three jets. A Bayesian neural network technique is used to discriminate between the signal and backgrounds, which are observed to be consistent with the standard model prediction. The 95% confidence level (CL) exclusion limits on anomalous right-handed vector, and left- and righthanded tensor Wtb couplings are measured to be |f R V | < 0.16, |f L T | < 0.057, and −0.049 < f R T < 0.048, respectively. For the FCNC couplings κtug and κtcg, the 95% CL upper limits on coupling strengths are |κtug|/Λ < 4.1 × 10−3 TeV−1 and |κtcg|/Λ < 1.8 × 10−2 TeV−1 , where Λ is the scale for new physics, and correspond to upper limits on the branching fractions of 2.0 × 10−5 and 4.1 × 10−4 for the decays t → ug and t → cg, respectively.